Kepemimpinan Negara dalam Perspektif Tafsīr Tanwīr Muhammadiyah - Egi Sukma Baihaki (Qur'an and Hadith Academic Society, 2020)
Humans are God's perfect creatures equipped with various abilities, not only physical but also spiritual. Humans are equipped with the potential and strength that can make it continue to exist in the world. The creation of humans to earth has a purpose as a leader. By using the literature study method it can be concluded that the position of humans as God's representatives on earth is equipped with various gifts so that humans can carry out their duties properly. The position that humans obtain is trust and devotion to God. Tafsīr Tanwīr mentions three potentials that exist in the human, namely the nature of shape, the nature of existence and the nature of potential. To become a leader on earth, humans must be able to develop a system of knowledge, social systems and artifact systems. Man must be fully aware that he is a being who has many statuses: as a superior person, as a servant of God, as a family member, as a member of society, as a citizen of the State, and as a citizen of the world